2016
DOI: 10.1177/0961000616668961
|View full text |Cite
|
Sign up to set email alerts
|

An interpretive structural modelling of the features influencing researchers’ selection of reference management software

Abstract: Reference management software packages are established as research software packages to help scholars organize their work, improve workflows and ultimately save time. The number of citation management software packages has increased in recent years and therefore choosing an appropriate one has become a challenge for researchers. Scholars always explore the features of an appropriate RMS prior to making an investment to invest in one. Hence, the purpose of this study was to identify and analyze the prominent fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
1
4
0
2
Order By: Relevance
“…Although several features noted as missing were also ranked as fairly unimportant, particularly the Web 2.0 social sharing and annotation features, there were two features ranked important by researchers that at least some noted as missing in their primary RMS: a cite while you write plugin and the ability to automatically generate a reference entry from a PDF. Although this survey did not ask researchers for their motivations in choosing an RMS, these responses can be interpreted as confirming previous work in this area, which found that researchers rate the ease of use and productivity of a tool as most important (Emanuel, 2013;Nilashi et al, 2016a).…”
Section: Discussionsupporting
confidence: 72%
“…Although several features noted as missing were also ranked as fairly unimportant, particularly the Web 2.0 social sharing and annotation features, there were two features ranked important by researchers that at least some noted as missing in their primary RMS: a cite while you write plugin and the ability to automatically generate a reference entry from a PDF. Although this survey did not ask researchers for their motivations in choosing an RMS, these responses can be interpreted as confirming previous work in this area, which found that researchers rate the ease of use and productivity of a tool as most important (Emanuel, 2013;Nilashi et al, 2016a).…”
Section: Discussionsupporting
confidence: 72%
“…DEMATEL involves steps such as direction and intensity measurement between factors, creation of an initial direct relation matrix, normalization and identification of cause-and-effect factors (Chang and Chen, 2018). A digraph map is created to show cause and effect, and important factors are found (Nilashi et al , 2019; Ortiz-Barrios et al , 2020). The steps are explained below in more detail:…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…The use of MCDM techniques is becoming more common (Zhu et al , 2019; Fu and Liao, 2019). The Fuzzy TOPSIS technique, as an MCDM strategy (Chen, 2000), has proved effective in identifying the optimal answer amid uncertainty (Mehta et al , 2019; Nilashi et al , 2019) from the perspective of experts. Using Fuzzy TOPSIS, this study identifies the most influential factors in senior citizens’ destination choice intentions.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Bilgi kaynaklarını bilimsel araştırma sürecinin akım merkezi haline getiren bu araçları/yazılımları/programları tanımlamak için yabancı literatürde bibliyografik asistan (bibliographic assistant) (Mueen Ahmed ve Al Dhubaib, 2011), bibliyografik atıf yönetimi yazılımı (bibliographic citation management software) (Steele, 2008), bibliyografik yönetim yazılımı (bibliographic management software) (Cuschieri, Grech ve Calleja, 2019;Fitzgibbons ve Meert, 2010;Ritterbush, 2007), bibliyografik yönetim aracı (bibliographic management tool) (Rempel ve Mellinger, 2015), bibliyografik yazılım (bibliographic software) (binti Zulkharnain ve Ashaari, 2015), bibliyografik araç (bibliographic tool) (Hull, Pettifer ve Kell, 2008), bibliyografik referans programı (bibliographical references program) (Kratochvíl, 2017), atıf ve bibliyografik veri tabanı yazılımı (citation and bibliographic database software) (Hernandez, El-Masri ve Hernandez, 2008), atıf yönetimi yazılımı (citation management software) (Hensley, 2011;Rakhshan, 2012), atıf yönetimi aracı (citation management tool) (Holt Zaugg, Richard E. West, Isaku Tateishi, Daniel L. Randall, 2011;Marino, 2012), atıf aracı (citation tool) (Childress, 2011), bilgi yönetimi yazılımı (information management software) (Fernandez, 2011), kişisel dosya yönetimi yazılımı (personal file management software) (Strube, Antoniewicz MLS, Glick MLS ve Asu, 1989), referans ve PDF yöneticisi yazılımı (reference and PDF-manager software) (Mead ve Berryman, 2010), referans yönetimi yazılımı (reference management software) (Basak, 2014;Fenner, 2010;Francese, 2013;Gilmour ve Cobus-Kuo, 2011;Lorenzetti ve Ghali, 2013;Melles ve Unsworth, 2015;Nilashi, Dalvi, Ibrahim, Zamani ve Ramayah, 2016;Tramullas, Sánchez-Casabón ve Garrido-Picazo, 2015), referans yönetimi aracı (reference management tool) (Zhang, 2012), sosyal referans yönetimi aracı (social reference management tool) ...…”
Section: Bireysel Kaynak Yönetimi Araçlarının Tanımıunclassified